Rendition of Proper Names in Translation: Transcription or Transliteration? - Ekotto, F.; Frehiwot, M. (My University, 2018)
All human languages have complex history with individual words. Speakers of any given language will often have occasion to self-consciously utilize another language’s terms within their speech. The paper deals with rendition of proper names in the process of translation. Our examples include personal first names, surnames, as well as general words which cause difficulties in the process of translation. In fact, the incorporation of foreign words into a language, has significant differences in terms of the different types of words, and different languages in different socio-political circumstances. We analyze this phenomenon in order to find out whether transliteration or transcription should be used in the process of translation. The transliteration system must be able to indicate graphical peculiarities that occur in translation process. It should be noted that many languages don’t have traditions of using their own script to represent foreign language words, but rather only represent these words phonetically. An international standard has evolved for precise phonetic transcription that goes by the abbreviation IPA, or International Phonetic Alphabet. Representing sound with scripts leaves room for disagreement as to the best representation in any given context. Each language is characterized by diverse spoken practices based upon regional location and social class. Thus, any phonetic scheme must be capable of representing the full spectrum of sounds possible in all variations. Any transcription scheme cannot possibly represent the language in general, but rather can only represent a specific dialect of the language at a specific time period. We came to conclusion that written sources are overall inconsistent in the degree to which they employ systematic transliteration or transcription schemes. With this regard, we consider three broad tendencies: inconsistency, term-based consistency, systematic consistency.
Seminar
Keywords: transcription; transliteration; proper names; inconsistency